The queen of poisons : a novel - Thorogood, Robert (Thorogood, Robert. Marlow Murder Club mystery., 2024)
"Geoffrey Lushington, Mayor of Marlow, dies suddenly during a town council meeting. When traces of aconite--also known as the queen of poisons--are found in his coffee cup, the police realize he was murdered. But who did it? And why? The police bring Judith, Suzie, and Becks in to investigate the murder as civilian advisors right from the start, so they have free rein to interview suspects and follow the evidence to their heart's content... which is perfect because Judith has no time for rules and standard procedure. But this case has the Marlow Murder Club stumped. Who would want to kill the affable mayor of Marlow? How did they even get the poison into his coffee? And is anyone else in danger? The Marlow Murder Club is about to face their most difficult case yet..."--